Enhancing Investigators’ Confidence in Crime Evidence Through Case Presentation and Reconstruction Techniques in Indonesia - Qaulan Sadida; Benny Sumardiana; Rohmat Rohmat; David Chuah Cee Wei (Jurnal Hukum Replik, 2025)
This research examines the crucial role of case presentation and reconstruction techniques in enhancing investigators' confidence in crime evidence. Given the complexities of modern criminal investigations, the clarity and precision of case titles are essential for effective communication and collaboration among law enforcement agencies. This study emphasizes the urgency of establishing standardized practices that improve the reliability of evidence interpretation, particularly in intricate cases where ambiguity can obstruct justice. This research contributed to the introduction of a systematic framework for developing case presentation that encapsulate key aspects of evidence and provide necessary contextual information. Furthermore, the study investigates advanced reconstruction techniques that visualize crime scenes and elucidate relationships among pieces of evidence, thereby facilitating a more comprehensive understanding of the case at hand. By integrating these components, investigators can make more informed decisions, ultimately enhancing the overall effectiveness of the investigative process. The implications of increased investigator confidence on case outcomes are also addressed, as such confidence can lead to more accurate conclusions, improved prosecution rates, and a heightened sense of justice for victims. The findings advocate for the incorporation of these innovative strategies within law enforcement training programs, aiming to address deficiencies in evidence assessment and foster a culture of precision and clarity in criminal investigations. By prioritizing the integration of effective case titles and reconstruction methodologies, this research seeks to advance the field of criminal justice and support the pursuit of truth in legal proceedings.